2013
DOI: 10.1111/aas.12247
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal chloroprocaine vs. lidocaine in day-case surgery: recovery, discharge and effect of pre-hydration on micturition

Abstract: Chloroprocaine is suitable for day-case surgery because of faster block regression and discharge than lidocaine. A 500 ml pre-load may not affect discharge but did not increase micturition problems for chloroprocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…In contrast, Breebaart et al 24 reported significantly shorter discharge times for chloroprocaine when compared with lidocaine. This discrepancy can be most probably attributed to the fact that in our study patients were deemed to be fit for discharge only once complete recovery from the sensory block had been achieved, whereas in the study of Breebaert et al, 24 patients were discharged once they were able to void and unassisted ambulation was possible.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In contrast, Breebaart et al 24 reported significantly shorter discharge times for chloroprocaine when compared with lidocaine. This discrepancy can be most probably attributed to the fact that in our study patients were deemed to be fit for discharge only once complete recovery from the sensory block had been achieved, whereas in the study of Breebaert et al, 24 patients were discharged once they were able to void and unassisted ambulation was possible.…”
Section: Discussionmentioning
confidence: 61%
“…31 Moreover, our data are in line with the results of studies in which fluid management was standardized and bladder volumes were measured. 24,25 A third limitation is the use of lower concentrations of local anesthetics, especially for bupivacaine, which were used in our study compared with other clinical trials. Although van Zundert et al 33 and Sheskey et al 34 concluded that the major determining factor for block height, motor block, and block duration is the dose of the local anesthetic and not the volume or the concentration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All these RCTs compared lidocaine with other local anesthetics (bupivacaine, prilocaine, mepivacaine, levobupivacaine, chloroprocaine, ropivacaine, procaine, articaine, or sameridine) and reported the incidence of TNS. We found that 28 RCTs had two groups [4][5][6][7][8][9][10][11][12]14,15,18,23,26,27,29,30,[34][35][36][37][38][39][40][41][42]44,46] of lidocaine more than other local anesthetics, while 11 RCTs had multiple groups [13,16,17,24,25,28,[31][32][33]43,45]. Five out of 11 RCTs have more than two lidocaine groups [16,24,28,33,43].…”
Section: Descriptions Of Trialsmentioning
confidence: 99%
“…The relationship between the incidence of TNS and baricity or concentration is shown in Figure 5. Sixteen studies used hyperbaric lidocaine [5,6,11,13,15,16,18,28,[32][33][34][35][36]39,42,45], 12 studies used isobaric [14,17,[23][24][25][26][27][29][30][31]41,44], and 4 studies used hypobaric lidocaine for spinal anesthesia [4,7,26,33]. One study had two treatment groups that administered hyperbaric or isobaric lidocaine [43].…”
Section: Outcome Synthesismentioning
confidence: 99%